Effect of Anemia in Pregnancy and its Perinatal Outcome: A Prospective Cohort Study - Pradhan, Noora; Tamrakar, Suman Raj; Karmacharya, Shailendra Bir (Journal of Lumbini Medical College, 2021)
Introduction: Anemia is a major risk factor for poor maternal health status. Anemia during pregnancy leads to poor birth outcomes such as fetal anemia, low birth weight, preterm birth, stillbirth, and neonatal mortality. This study aimed to assess the effect of anemia in pregnancy and its perinatal outcome. Methods: A prospective study was conducted among 370 pregnant women in Dhulikhel Hospital, Kavre from June 2017 to December 2017. Descriptive statistics were used to represent the socio-clinical characteristics. Bivariate analysis was performed to analyze the effect of anemia. Results: The study found that all the participants were anemic out of which mild anemia was observed in 352 (95.4%), moderate anemia in 17 (4.6%), and severe anemia in one (0.3%) participants respectively. Women aged 17 to 24 years and multiparous women had higher odds of having moderate anemia (Hb 7.0-8.9 g/dL). Women with moderate anemia had more odds of having neonates with less Apgar scores. Women with moderate anemia had nine times higher odds of having newborn mortality. Conclusion: Anemia during pregnancy not only affects the health status of the mother but also impacts the birth outcomes. This study highlighted the emphasis on the active participation of governmental and non-governmental organizations to prevent adverse effects of anemia during pregnancy and birth outcomes.